Theological education in the Latin American context. From the contributions of Juan Luis Segundo (PONTIFICIA UNIV CATOLICA CHILE, FACULTAD TEOLOGIA, 2016)
Considering the requirements for a theological formation in the current Latin-American context shaped by globalization, the author gathers up some important elements of Juan Luis Segundo's theology, because he considers they are still relevant. Among the characteristics that the author highlights of this remarkable father of the Latin-American Theology -who passed away two decades ago-is the early and lucid attention that Segundo paid to the correct articulation between faith and cultures. Also, the emphasis on the humanizing objective of Theology, as well as the critical and liberating purposes of it. Another important element is the impetus that gave to a Theology based on reality, which answers questions made by believers and forms adults in faith. Christians adults in faith that are able to continue learning and dealing with new challenges on a constantly changing context.